A Time To Shine: How Business Interruption Micro Takaful Scheme Step Up To Covid-19 For Micro Enterprises In Malaysia - SALLEH, FAUZILAH; DAUD, WAN NORHAYATE WAN; NOOR, NOOR AINA AMIRAH MOHD (The journal of contemporary issues in business and government, 2021)
After a series of disasters, including major floods, landslides, and hurricanes, Malaysia was affected by multiple damages and losses. Moreover, with the proclamation of the Movement Control Order (MCO) by the government, the COVID-19 pandemic has led to widespread economic disruption across the country. By this year, Malaysia's Gross Domestic Product (GDP) is projected to contract between 0.1 per cent and 4.6 per cent. However, this projection may be negatively impacted due to the closures of short-term business, sales losses, and the downturn in revenue. In Malaysia, the Micro, Small and Medium Enterprises (MSMEs) amounted to 907,765, in which 693,679 (76.5%) comprised of microenterprises (MEs). After ceasing their operations, these MEs and businesses were prone to bankruptcy, in which MEs were severely affected by the MCO. Therefore, this article investigated the coverage of existing insurance schemes of business interruption losses, formulated the business protection schemes against business losses by observing the effects of COVID-19, and the requirements of takaful/insurance protection, particularly on MEs in Malaysia. Hence, this article focused on business interruption during a pandemic, which involved microbusiness interruption scheme for MEs in Malaysia.